2018
DOI: 10.2147/ijwh.s143510
|View full text |Cite
|
Sign up to set email alerts
|

WaLIDD score, a new tool to diagnose dysmenorrhea and predict medical leave in university students

Abstract: BackgroundDysmenorrhea is a frequent and misdiagnosed symptom affecting the quality of life in young women. A working ability, location, intensity, days of pain, dysmenorrhea (WaLIDD) score was designed to diagnose dysmenorrhea and to predict medical leave.MethodsThis cross-sectional design included young medical students, who completed a self-administered questionnaire that contained the verbal rating score (VRS; pain and drug subscales) and WaLIDD scales. The correlation between scales was established throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 17 publications
1
37
0
1
Order By: Relevance
“…The WaLIDD score contained three frequently used criteria identified in the definitions of dysmenorrhea present in the literature: days of pain (D), work ability (Wa), and anatomical region of pain location (L). 11 Study reported that about 16% of the students had symptoms which were severe enough for them to be absent from college.…”
Section: Discussionmentioning
confidence: 99%
“…The WaLIDD score contained three frequently used criteria identified in the definitions of dysmenorrhea present in the literature: days of pain (D), work ability (Wa), and anatomical region of pain location (L). 11 Study reported that about 16% of the students had symptoms which were severe enough for them to be absent from college.…”
Section: Discussionmentioning
confidence: 99%
“…The results for the prevalence of dysmenorrhea and its effect on academic activities will be published elsewhere. The severity of dysmenorrhea was assessed using WaLIDD scale [ 20 ]. WaLIDD score measures the severity of dysmenorrhea on a scale of 0–12 with scores 0, 1–4, 5–7, and 8–12 representing no, mild, moderate and severe dysmenorrhea, respectively [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The severity of dysmenorrhea was assessed using WaLIDD scale [ 20 ]. WaLIDD score measures the severity of dysmenorrhea on a scale of 0–12 with scores 0, 1–4, 5–7, and 8–12 representing no, mild, moderate and severe dysmenorrhea, respectively [ 20 ]. A five-point Likert scale was used to assess the student’s perceptions towards analgesics and CATs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other measures of dysmenorrhea pain have not fully captured symptom interference. For example, one measure assessed "working ability" as the only dysmenorrhea impact (Teheran et al, 2018), while another only assessed impact on "things the person usually does" without asking what specific aspects of life are affected (Wyrwich et al, 2018). Pain interference with daily activities has been acknowledged as a core outcome in pain research, especially in clinical trials (Dworkin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%